The Relationship of Motivation and Self-regulated Learning through Blended Learning in the Covid-19 Era - Fitria Herliana; Elisa Elisa; Ahmad Farhan; I Made Astra (STKIP Singkawang, 2022)
This study aims to determine the relationship between motivation and self-regulated learning through blended learning in the covid-19 era. This study is a quantitative study with correlation study type. Samples were taken using random sampling techniques from all 1st-semester students who took basic physics courses and obtained 67 students consisting of 3 classes. The data was collected using the instrument of motivation and self-regulated learning in the form of a questionnaire which was filled in by the students after participating in basic physics courses using blended learning. The data that has been collected is then analyzed for normality and linearity. The data shows the results are normally distributed and linear so that data analysis can be continued with hypothesis testing using the Pearson product-moment correlation test and the value of R = 0.897 is obtained which is then compared with the R table at a significant level of 0.05, namely 0.244. Because R (0.897)> R table (0.244), it can be concluded that there is a positive relationship between motivation and self-regulated learning with the correlation coefficient value is 0.897 which is classified as very strong. Therefore, students' motivation and self-regulated learning through blended learning in the covid-19 era have a very strong relationship. This could be of concern to teachers and lecturers as facilitators in learning in this Covid-19 era. It is hoped that interesting learning using a blended learning approach can be applied so that student learning motivation increases and has a direct effect on students' desire to manage their own learning.